Effect of behavior change communication through the health development army on birth weight of newborns in Ambo district, Ethiopia: a cluster randomized controlled community trial - Mitsiwat Abebe Gebremichael; Tefera Belachew Lema (BMC, 2024)
Abstract Background Poor behavior change communication on maternal nutrition and health throughout pregnancy is thought to be to blame for Ethiopia's high rate of low birthweight babies, and this has implications for neonatal morbidity and mortality. The effect of behavior change communication on birth weight in the study district was not examined. This study was to determine whether improving neonatal birthweight using nutrition and health behavior change communication (NHBCC) interventions was successful. Methods A cluster randomized controlled trial was conducted in the Ambo district of Ethiopia from May 5, 2018-January 30, 2019. At the beginning of the study, 385 women in the 24 intervention groups and 385 women in the 24 control groups were recruited. In the intervention group, health development armies delivered the NHBCC core message every two weeks for four months by grouping pregnant women in specific clusters. Pregnant women in the control group received the routine treatment offered by the healthcare system during their ANC visits. Within 24 h of birth, the birthweights of 302 and 292 neonates in the intervention and control groups, respectively, were measured at the end point of the study. A binary generalized linear model analysis was employed. Result The control group had a larger absolute risk of neonates with low birthweight (0.188 vs. 0.079, p < 0.001) than the intervention group. Pregnant women in the intervention group had an absolute risk difference of 10.9% for low birthweight. Pregnant women who received the intervention were 62% less likely to have low-risk birthweight compared to pregnant women who were in the control group (ARR = 0.381, 95% CI: 0.271-0.737). Conclusion Nutrition and health behavior change Communication by health development armies improves birthweight. The findings demonstrated that to improve birthweight, NHBCC must be administered to pregnant women in groups via health development armies in their communities. Trial registration number PACTR201805003366358.